Nivel de cumplimiento de las Buenas Prácticas de Almacenamiento en una droguería de Trujillo, 2017 - Sifuentes Gonzales, Kris Caroline (2020)
In this report, the level of compliance with Good Storage Practices (GSP) in a Trujillo drugstore was analyzed based on the percentage of compliance with the indicators for each of the factors considered for GSP. It was considered that a value greater than 80% represents a high level, between 50% and 80% a medium level and less than 50% a low level. For the analysis of the level of compliance with GSP, use was made of the Inspection Guide for drug stores, specialized warehouses and customs warehouses that preserve pharmaceutical products, medical devices and health products, carried out by the General Directorate of Medicines, Supplies and Drugs. From the analyzed data, the following results were obtained: regarding factor 1 regarding quality assurance, factor 2 that analyzed the staff, factor 3 that referred to the premises facilities, factor 6 that verified the degree of claims, and factor 8 that was in charge of verifying the self-inspections reached a compliance percentage of 100%, factor 4 that verified the warehouse conditions obtained 95% compliance; factor 5 regarding documentation obtained an average value of 80% in its compliance and factor 7 that analyzed the area of withdrawal from the market obtained the lowest percentage (75%) in the study. It was concluded that the level of compliance with Good Storage Practices was high with 93.8%